Evaluation of mass drug administration for schistosomiasis and soil-transmitted helminths in school-aged children in Bankass, Mali - Moussa Sangare (Elsevier, 2021)
Background: In 2004, Mali implemented mass drug administration (MDA) aimed at controlling schistosomiasis and soil-transmitted helminths. Despite several rounds of MDA, the health district of Bankass reported low coverage (64.8%) for praziquantel and albendazole in 2017, meaning that this district was still facing challenges in accomplishing the targeted 75% coverage. This study aimed to explore the barriers and gaps that hindered MDA implementation in Bankass. Methods: A cross-sectional study was performed. Questionnaires were administrated to all school-aged children in randomly selected villages. Technical directors of community health centers and community drug distributors in the selected villages were included in the interviews. Results: A total of 2128 children and 52 health workers were interviewed. Coverage rates were 93.51% (1990/2128) for praziquantel and 95.25% (2027/2128) for albendazole. Among the untreated children, 31.63% (31/98) reported being unaware of the campaign and 26.53% (26/98) were unable to reach the distribution points. Most of the health workers suggested increasing incentives. Conclusion: The data showed satisfactory coverage >90%, in contrast with lower rates initially reported by the district health information system. These results raise concerns about the reliability of programmatic data and highlight the importance of population-based surveys for the evaluation of control interventions.